A Revision of the Drosophila spinipes Species Group (Diptera: Drosophilidae) - Grimaldi, David A.; Jones, Lance E. (Zootaxa, 2020)
Two African drosophilids have distinctive protarsal spines in both sexes: Drosophila spinipes Lamb, 1914 from the Seychelles and D. suma Burla, 1954 from the Ivory Coast. Both were later classified in the genus Hirtodrosophila Duda of the Zygothrica genus group, and suma synonymized under spinipes by Tsacas (2006). We resurrect suma from synonymy, define the spinipes species group, and add seven new species in the group from Africa and Madagascar: Drosophila cameroonensis n. sp., D. freidbergi n. sp., D. hypandrilata n. sp., D. jambiya n. sp., D. malagasy n. sp., D. nigrospinipes n. sp., and D. phalloserra n. sp. Another four species are reported but not described. Detailed morphology informs that these anthophilous flies do not belong to the Zygothrica genus group, and they are returned to the genus Drosophila (unplaced to subgenus), albeit primitive members with some very distinctive specialized features. All distribution records, published and new, are presented along with a key to all nine named species.